Antibacterial, antistatic, flame-retardant polystyrene composite material and preparation method thereof
By combining the nanosilver-loaded cucurbiturium grafted carbon nanotubes with adamantane/cyclotriphosphazene modified carbon fiber felt in polystyrene materials, a three-dimensional mesh material was formed, which solved the problem of insufficient antibacterial, antistatic and flame retardant properties of polystyrene materials, and achieved higher comprehensive performance and application value.
Patent Information
- Application Number
- CN202510127034.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polystyrene materials are easily contaminated by bacteria during use, and are prone to static electricity and flammable, posing health and safety hazards.
By esterification reaction with monohydroxycucurbiturate and carboxylated carbon nanotubes, nanosilver-loaded cucurbiturate grafted carbon nanotubes were obtained, and combined with adamantane/cyclotriphosphazene modified carbon fiber felt to form a three-dimensional mesh material. Finally, the polystyrene melt penetrated into the network to prepare antibacterial, antistatic, flame-retardant polystyrene composite material.
This composite material not only has good antibacterial properties, antistatic properties and flame retardant properties, but also improves conductivity and fill cloth, enhances overall performance, and is suitable for a variety of application scenarios.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modified plastics and provides an antibacterial, antistatic and flame-retardant polystyrene composite material and a preparation method thereof. Background Art
[0002] Polystyrene is a thermoplastic with excellent comprehensive properties. It has good transparency and chemical stability, is easy to shape and process, and is suitable for various molding methods such as injection molding, extrusion, blister molding and foaming. It is also lightweight, high-strength and low-cost. Currently, polystyrene materials have been widely used in the fields of electronic appliances, building materials, packaging materials, etc.
[0003] During use, polystyrene products are easily contaminated by bacteria and other microorganisms, posing a threat to health, so they need to be given antibacterial properties. At present, the main method to improve the antibacterial properties of plastics is to add antibacterial agents, such as silver-based, zinc-based and other inorganic antibacterial agents. Among them, nanosilver has a strong inhibitory and killing effect on dozens of pathogenic microorganisms, and does not produce drug resistance, making it a commonly used antibacterial additive.
[0004] Polystyrene itself has good insulation properties, so its products are prone to static electricity on the surface during processing, transportation and use, resulting in contamination of dust, debris and other small debris, and may also cause electric shock, spark discharge and other phenomena, posing a safety hazard, so it is necessary to give it an antistatic effect. Currently, the commonly used methods include adding antistatic agents to the plastic matrix and coating the plastic surface with antistatic coatings or films.
[0005] In addition, polystyrene is a flammable material and is prone to dripping during combustion, releasing a large amount of heat, smoke and toxic gases. With the widespread application of polystyrene, research on polystyrene materials with flame retardant properties is of great significance for reducing its fire hazard and expanding its application areas. The commonly used method is to give polystyrene certain flame retardant properties by adding flame retardants. Summary of the invention
[0006] In view of the above, the present invention proposes an antibacterial, antistatic, flame retardant polystyrene composite material and a preparation method, in order to obtain a polystyrene composite material with better comprehensive performance and higher application value.
[0007] To achieve the above purpose, the specific technical solution of the present invention is as follows: First, the present invention proposes a method for preparing an antibacterial, antistatic, flame-retardant polystyrene composite material, comprising the following preparation steps: S1, using monohydroxycucurbituril [7] to carry out esterification reaction with carboxylated carbon nanotubes to obtain cucurbituril-grafted carbon nanotubes; Preferably, the specific preparation process is: 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine, and N,N'-dicyclohexylcarbodiimide are added to a dimethyl sulfoxide dispersion of carboxylated carbon nanotubes, vacuumized and introduced with nitrogen, and then a dimethyl sulfoxide solution of monohydroxycucurbituril [7] is added dropwise, reacted at 20° C. for 15-25 hours, centrifuged, washed with sodium chloride solution, and vacuum dried to obtain cucurbituril-grafted carbon nanotubes; S2, adding the silver nitrate solution to the cucurbituril grafted carbon nanotube aqueous dispersion, reacting at 25° C. for 20-40 minutes, then adding the sodium borohydride solution dropwise while stirring, continuing the reaction for 150-200 minutes, filtering, washing with deionized water, and vacuum drying to obtain the cucurbituril grafted carbon nanotubes loaded with nanosilver; S3, adding hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and 2 / 3 triethylamine to dichloromethane, reacting at 30-35°C for 10-15h, then immersing in amino-modified carbon fiber felt, adding 1 / 3 triethylamine, continuing to react under ultrasonic treatment for 6-8h, taking out and ultrasonically treating in deionized water for 2-3h, freeze-drying to obtain adamantane / cyclotriphosphazene modified carbon fiber felt; S4, dispersing the cucurbituril-grafted carbon nanotubes loaded with nanosilver in deionized water, immersing in adamantane / cyclotriphosphazene modified carbon fiber felt, stirring and reacting at 25° C. for 2.5-3.5 days, taking out and ultrasonically treating in deionized water for 2-3 hours, and freeze-drying to obtain a carbon fiber / carbon nanotube three-dimensional network material; S5. Heat and melt the polystyrene, infiltrate it into the network of the carbon fiber / carbon nanotube three-dimensional mesh material under vacuum assistance, cool and solidify it, and obtain an antibacterial, antistatic, flame-retardant polystyrene composite material.
[0008] Cucurbituril is a macrocyclic compound formed by glycoluril units connected by methylene groups. Its unique structure contains a hydrophobic cavity, which can serve as the main body of host-guest interaction. The present invention uses cucurbituril [7] containing a hydroxyl group in its structure. First, the hydroxyl group is used to undergo an esterification reaction with the carboxyl group on the surface of the carboxylated carbon nanotube to graft cucurbituril [7] onto the surface of the carbon nanotube (i.e., S1), and then adsorbs Ag. + , Ag is reacted with sodium borohydride + Reduced to nano-silver (ie, S2), cucurbituril-grafted carbon nanotubes loaded with nano-silver are obtained.
[0009] Preferably, in S1, the mass ratio of monohydroxycucurbituril [7] to carboxylated carbon nanotubes is 2-3:1.
[0010] Preferably, in S1, the molar ratio of monohydroxycucurbituril [7], 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine, and N,N'-dicyclohexylcarbodiimide is 1:10-15:10-15:10-15. Furthermore, the concentration of the dimethyl sulfoxide solution of monohydroxycucurbituril [7] is 4-6 g / L; the concentration of the dimethyl sulfoxide dispersion of the carboxylated carbon nanotubes is 0.8-1.2 g / L.
[0011] Preferably, in S2, the mass ratio of cucurbituril grafted carbon nanotubes, silver nitrate, and sodium borohydride is 1:0.4-0.6:6-8. Further, the concentration of the cucurbituril grafted carbon nanotube aqueous dispersion is 0.5-1 g / L; the concentration of the silver nitrate solution is 1-1.5 g / L; and the concentration of the sodium borohydride solution is 15-25 g / L.
[0012] The structure of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene not only contains a cyclotriphosphazene structure and has a PN flame retardant effect, but also contains six epoxy groups that can react with amino groups. In the present invention S3, 1-adamantanethylamine is first used to react with some epoxy groups of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene to graft the adamantane structure onto the cyclotriphosphazene derivative, and then amino-modified carbon fiber felt is used to react with the remaining epoxy groups of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene to graft the cyclotriphosphazene structure onto the surface of the carbon fiber to obtain adamantane / cyclotriphosphazene modified carbon fiber felt.
[0013] Preferably, in S3, the molar ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and triethylamine is 1:3-4:0.2-0.4. Further preferably, in S3, the mass ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, amino-modified carbon fiber felt, and dichloromethane is 0.4-0.6:1:100-150.
[0014] In the present invention, S4, the host-guest hydrophobic interaction between cucurbituril and adamantane groups is used to make adamantane / cyclotriphosphazene modified carbon fibers and cucurbituril grafted carbon nanotubes loaded with nano-silver self-assemble to form a three-dimensional mesh material. S5, a polystyrene melt is infiltrated into the network of the three-dimensional mesh material and cooled and solidified to obtain a polystyrene composite material.
[0015] Preferably, in S4, the mass ratio of the cucurbituril-grafted carbon nanotubes loaded with nanosilver, the adamantane / cyclotriphosphazene modified carbon fiber felt, and deionized water is 0.8-1:1:100-150.
[0016] The present invention also provides an antibacterial, antistatic and flame-retardant polystyrene composite material prepared by the above-mentioned preparation method. The polystyrene composite material is composed of polystyrene, adamantane / cyclotriphosphazene modified carbon fibers and cucurbituril grafted carbon nanotubes loaded with nano-silver, wherein the adamantane / cyclotriphosphazene modified carbon fibers and the cucurbituril grafted carbon nanotubes loaded with nano-silver self-assemble to form a three-dimensional network structure, and the polystyrene is filled and distributed in the network.
[0017] The present invention provides an antibacterial, antistatic, flame-retardant polystyrene composite material and a preparation method thereof, which has the following beneficial effects: In the polystyrene composite material prepared by the present invention, firstly, the three-dimensional network structure formed by carbon fiber and carbon nanotube can improve the conductivity of the composite material, and the presence of nanosilver can further reduce the resistivity, so that the composite material has good antistatic performance; secondly, nanosilver can give the composite material good antibacterial property, and carbon nanotube can also play a certain antibacterial role; thirdly, the cyclotriphosphazene structure has PN flame retardant effect, and carbon nanotube can prevent further combustion by forming a protective layer during the combustion process, and the combination of the two can give the composite material good flame retardant performance. It can be seen that the polystyrene composite material prepared by the present invention has good antibacterial performance, antistatic performance and flame retardant performance. DETAILED DESCRIPTION
[0018] The following specific examples are further explanations of the technical solutions of the present invention, but it should not be understood that the scope of the present invention is limited to the following examples.
[0019] The raw materials involved in the following examples are: Monohydroxycucurbituril [7] was prepared by referring to the prior art, specifically referring to the ammonium persulfate oxidation method in "Design of trimethyllysine fluorescent probe and methylated peptide enrichment material based on cucurbituril [7]", and the concentration of dimethyl sulfoxide solution of monohydroxycucurbituril [7] was 5 g / L.
[0020] Hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene was prepared by referring to the prior art, with specific reference to 2.2.3-2.2.4 in "Preparation of Bio-based Flame-retardant Epoxy Resin Based on Eugenol and Study on Its Flame-retardant Mechanism".
[0021] Carboxylated carbon nanotubes were purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., with a length range of 0.5-2 μm and a diameter range of 30-50 nm. The concentration of dimethyl sulfoxide dispersion of carboxylated carbon nanotubes was 1 g / L. Amino-modified carbon fiber felt was purchased from Shanghai Lishuo Composite Materials Technology Co., Ltd., with a density of 0.2 g / cm 3 The thickness is 3 mm. Polystyrene was purchased from Shanghai Hehongcheng Plastic Technology Co., Ltd., with the brand name PH-55Y.
[0022] Other raw materials are common commercially available products. Example 1
[0023] S1. Add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide to a dimethyl sulfoxide dispersion of carboxylated carbon nanotubes, evacuate and introduce nitrogen, then drop a dimethyl sulfoxide solution of monohydroxycucurbituril [7], react at 20°C for 20 hours, centrifuge, wash with sodium chloride solution and vacuum dry to obtain cucurbituril-grafted carbon nanotubes; the mass ratio of monohydroxycucurbituril [7] to carboxylated carbon nanotubes is 2.5:1; the molar ratio of monohydroxycucurbituril [7], 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide is 1:10:15:12; S2, adding silver nitrate solution (concentration of 1.5 g / L) to cucurbituril grafted carbon nanotube aqueous dispersion (concentration of 0.5 g / L), reacting at 25°C for 30 min, then adding sodium borohydride solution (concentration of 20 g / L) dropwise while stirring, continuing the reaction for 180 min, filtering, washing with deionized water, and vacuum drying to obtain cucurbituril grafted carbon nanotubes loaded with nanosilver; the mass ratio of cucurbituril grafted carbon nanotubes, silver nitrate, and sodium borohydride is 1:0.4:6; S3, add hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and 2 / 3 triethylamine to dichloromethane, react at 35°C for 12 hours, then immerse in amino-modified carbon fiber felt, add 1 / 3 triethylamine, continue to react under ultrasonic treatment for 8 hours, take out and ultrasonically treat in deionized water for 2 hours, freeze-dry to obtain adamantane / cyclotriphosphazene modified carbon fiber felt; the molar ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and triethylamine is 1:4:0.4; the mass ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, amino-modified carbon fiber felt, and dichloromethane is 0.4:1:120; S4, dispersing the nanosilver-loaded cucurbituril-grafted carbon nanotubes in deionized water, immersing in adamantane / cyclotriphosphazene-modified carbon fiber felt, stirring and reacting at 25°C for 3 days, taking out and ultrasonically treating in deionized water for 3 hours, freeze-drying, and obtaining a carbon fiber / carbon nanotube three-dimensional network material; the mass ratio of the nanosilver-loaded cucurbituril-grafted carbon nanotubes, adamantane / cyclotriphosphazene-modified carbon fiber felt, and deionized water is 1:1:150; S5. Heat and melt the polystyrene, infiltrate it into the network of the carbon fiber / carbon nanotube three-dimensional mesh material under vacuum assistance, cool and solidify it, and obtain an antibacterial, antistatic, flame-retardant polystyrene composite material. Example 2
[0024] S1. Add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide to a dimethyl sulfoxide dispersion of carboxylated carbon nanotubes, evacuate and introduce nitrogen, then drop a dimethyl sulfoxide solution of monohydroxycucurbituril [7], react at 20°C for 20 hours, centrifuge, wash with sodium chloride solution and vacuum dry to obtain cucurbituril-grafted carbon nanotubes; the mass ratio of monohydroxycucurbituril [7] to carboxylated carbon nanotubes is 2.5:1; the molar ratio of monohydroxycucurbituril [7], 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide is 1:12:12:15; S2, adding silver nitrate solution (concentration of 1 g / L) to cucurbituril grafted carbon nanotube aqueous dispersion (concentration of 1 g / L), reacting at 25°C for 35 minutes, then adding sodium borohydride solution (concentration of 15 g / L) dropwise while stirring, continuing the reaction for 160 minutes, filtering, washing with deionized water, and vacuum drying to obtain cucurbituril grafted carbon nanotubes loaded with nanosilver; the mass ratio of cucurbituril grafted carbon nanotubes, silver nitrate, and sodium borohydride is 1:0.5:7; S3, add hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and 2 / 3 triethylamine to dichloromethane, react at 30°C for 15 hours, then immerse in amino-modified carbon fiber felt, add 1 / 3 triethylamine, continue to react under ultrasonic treatment for 8 hours, take out and ultrasonically treat in deionized water for 2 hours, freeze-dry, and obtain adamantane / cyclotriphosphazene modified carbon fiber felt; the molar ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and triethylamine is 1:4:0.4; the mass ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, amino-modified carbon fiber felt, and dichloromethane is 0.5:1:150; S4, dispersing the nanosilver-loaded cucurbituril-grafted carbon nanotubes in deionized water, immersing in adamantane / cyclotriphosphazene-modified carbon fiber felt, stirring and reacting at 25°C for 3 days, taking out and ultrasonically treating in deionized water for 2 hours, freeze-drying, and obtaining a carbon fiber / carbon nanotube three-dimensional network material; the mass ratio of the nanosilver-loaded cucurbituril-grafted carbon nanotubes, adamantane / cyclotriphosphazene-modified carbon fiber felt, and deionized water is 1:1:150; S5. Heat and melt the polystyrene, infiltrate it into the network of the carbon fiber / carbon nanotube three-dimensional mesh material under vacuum assistance, cool and solidify it, and obtain an antibacterial, antistatic, flame-retardant polystyrene composite material. Example 3
[0025] S1. Add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide to a dimethyl sulfoxide dispersion of carboxylated carbon nanotubes, evacuate and introduce nitrogen, then drop a dimethyl sulfoxide solution of monohydroxycucurbituril [7], react at 20°C for 20 hours, centrifuge, wash with sodium chloride solution and vacuum dry to obtain cucurbituril-grafted carbon nanotubes; the mass ratio of monohydroxycucurbituril [7] to carboxylated carbon nanotubes is 2.5:1; the molar ratio of monohydroxycucurbituril [7], 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide is 1:15:10:10; S2, adding silver nitrate solution (concentration of 1.2 g / L) to cucurbituril grafted carbon nanotube aqueous dispersion (concentration of 0.8 g / L), reacting at 25°C for 25 min, then adding sodium borohydride solution (concentration of 25 g / L) dropwise while stirring, continuing the reaction for 200 min, filtering, washing with deionized water, and vacuum drying to obtain cucurbituril grafted carbon nanotubes loaded with nanosilver; the mass ratio of cucurbituril grafted carbon nanotubes, silver nitrate, and sodium borohydride is 1:0.6:8; S3, add hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and 2 / 3 triethylamine to dichloromethane, react at 33°C for 13 hours, then immerse in amino-modified carbon fiber felt, add 1 / 3 triethylamine, continue to react under ultrasonic treatment for 8 hours, take out and ultrasonically treat in deionized water for 3 hours, freeze-dry to obtain adamantane / cyclotriphosphazene modified carbon fiber felt; the molar ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and triethylamine is 1:4:0.4; the mass ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, amino-modified carbon fiber felt, and dichloromethane is 0.6:1:135; S4, dispersing the nanosilver-loaded cucurbituril-grafted carbon nanotubes in deionized water, immersing in adamantane / cyclotriphosphazene-modified carbon fiber felt, stirring and reacting at 25°C for 3 days, taking out and ultrasonically treating in deionized water for 2 hours, freeze-drying, and obtaining a carbon fiber / carbon nanotube three-dimensional network material; the mass ratio of the nanosilver-loaded cucurbituril-grafted carbon nanotubes, adamantane / cyclotriphosphazene-modified carbon fiber felt, and deionized water is 1:1:150; S5. Heat and melt the polystyrene, infiltrate it into the network of the carbon fiber / carbon nanotube three-dimensional mesh material under vacuum assistance, cool and solidify it, and obtain an antibacterial, antistatic, flame-retardant polystyrene composite material.
[0026] Performance Testing: (1) The polystyrene composite material prepared in the example was cut into disc samples with a diameter of 12 mm. The test bacteria were Escherichia coli and Staphylococcus aureus. 0.1 mL of bacterial solution (108 CFU / mL) was evenly spread on the agar plate, the disc sample was placed on the agar surface, and placed in a constant temperature incubator at 37℃ for 24h, the outer diameter of the inhibition zone was measured, and the radius of the inhibition zone was calculated according to the following formula: radius of inhibition zone = (outer diameter of inhibition zone - diameter of sample) / 2.
[0027] (2) The surface resistivity of the polystyrene composite material prepared in accordance with the GB / T 1410-2006 standard test example was measured (the material was placed in an environment with a temperature of 23°C and a relative humidity of 50% for 24 hours before the test) to characterize the antistatic properties of the material.
[0028] (3) The limiting oxygen index of the polystyrene composite material prepared in accordance with the test examples of GB / T 2406-2008 and the UL-94 vertical burning rating of the polystyrene composite material prepared in accordance with the test examples of GB / T 2408-2021 are used to characterize the flame retardant properties of the materials.
[0029] The data obtained from the above tests are recorded in Table 1.
[0030] Table 1:
Claims
1. A method for preparing an antibacterial, antistatic, flame-retardant polystyrene composite material, characterized in that: The method comprises the following preparation steps: S1, using monohydroxycucurbituril [7] to carry out esterification reaction with carboxylated carbon nanotubes to obtain cucurbituril-grafted carbon nanotubes; S2, adding the silver nitrate solution to the cucurbituril grafted carbon nanotube aqueous dispersion, reacting at 25° C. for 20-40 minutes, then adding the sodium borohydride solution dropwise while stirring, continuing the reaction for 150-200 minutes, filtering, washing with deionized water, and vacuum drying to obtain the cucurbituril grafted carbon nanotubes loaded with nanosilver; S3, adding hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine, and 2 / 3 triethylamine to dichloromethane, reacting at 30-35°C for 10-15h, then immersing in amino-modified carbon fiber felt, adding 1 / 3 triethylamine, continuing to react under ultrasonic treatment for 6-8h, taking out and ultrasonically treating in deionized water for 2-3h, freeze-drying to obtain adamantane / cyclotriphosphazene modified carbon fiber felt; S4, dispersing the cucurbituril-grafted carbon nanotubes loaded with nanosilver in deionized water, immersing in adamantane / cyclotriphosphazene modified carbon fiber felt, stirring and reacting at 25° C. for 2.5-3.5 days, taking out and ultrasonically treating in deionized water for 2-3 hours, and freeze-drying to obtain a carbon fiber / carbon nanotube three-dimensional network material; S5. Heat and melt the polystyrene, infiltrate it into the network of the carbon fiber / carbon nanotube three-dimensional mesh material under vacuum assistance, cool and solidify it, and obtain an antibacterial, antistatic, flame-retardant polystyrene composite material.
2. The preparation method according to claim 1, characterized in that: The specific preparation process of cucurbituril grafted carbon nanotubes in S1 is as follows: 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide are added to a dimethyl sulfoxide dispersion of carboxylated carbon nanotubes, the mixture is evacuated and nitrogen is introduced, and then a dimethyl sulfoxide solution of monohydroxycucurbituril [7] is added dropwise, reacted at 20°C for 15-25h, and the mixture is centrifuged, washed with sodium chloride solution and dried in vacuum to obtain cucurbituril grafted carbon nanotubes.
3. The preparation method according to claim 2, characterized in that: The mass ratio of monohydroxycucurbituril[7] and carboxylated carbon nanotubes is 2-3:
1.
4. The preparation method according to claim 2, characterized in that: The molar ratio of monohydroxycucurbituril [7], 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and N,N'-dicyclohexylcarbodiimide is 1:10-15:10-15:10-15; the concentration of the dimethyl sulfoxide solution of monohydroxycucurbituril [7] is 4-6 g / L; the concentration of the dimethyl sulfoxide dispersion of carboxylated carbon nanotubes is 0.8-1.2 g / L.
5. The preparation method according to claim 1, characterized in that: The mass ratio of cucurbituril grafted carbon nanotubes, silver nitrate and sodium borohydride in S2 is 1:0.4-0.6:6-8.
6. The preparation method according to claim 1, characterized in that: The concentration of the cucurbituril grafted carbon nanotube aqueous dispersion in S2 is 0.5-1 g / L; the concentration of the silver nitrate solution is 1-1.5 g / L; and the concentration of the sodium borohydride solution is 15-25 g / L.
7. The preparation method according to claim 1, characterized in that: The molar ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, 1-adamantanethamine and triethylamine in S3 is 1:3-4:0.2-0.
4.
8. The preparation method according to claim 1, characterized in that: The mass ratio of hexa[(4-epoxypropyl-2-methoxy)phenoxy]cyclotriphosphazene, amino-modified carbon fiber felt and dichloromethane in S3 is 0.4-0.6:1:100-150.
9. The preparation method according to claim 1, characterized in that: The mass ratio of the cucurbituril-grafted carbon nanotube loaded with nano-silver, the adamantane / cyclotriphosphazene-modified carbon fiber felt, and the deionized water in S4 is 0.8-1:1:100-150.
10. The antibacterial, antistatic and flame-retardant polystyrene composite material prepared by the preparation method according to any one of claims 1 to 9.